Legal protection for reporting witnesses in matters of narcotics and psychotropics - Arif Budi Setiawan (Requisitoire Law Enforcement, 2022)
In writing this thesis, the writer discusses the issue of Legal Protection for Reporting Witnesses in the matter of Narcotics and Psychotropics. As an effort to find out the form of legal protection provided by the Police to reporting witnesses and to find out the methods and capabilities of law enforcement officials or the police in providing protection in accordance with Law No. 22 of 1997 and Health Law No. 23 of 1992 and provide an explanation of the rule of law and side effects Narcotics and psychotropics, as well as legal sanctions for reporting witnesses who know about the crime of Narcotics but do not report and legal sanctions for officers who do not shoot reporting reports. So the approach method used is sociological juridical, studying the applicable legal provisions and the reality that occurs in practice. Then all existing data were analyzed descriptively qualitatively. Based on the research, the authors get answers to existing problems that legal protection for witnesses means providing protection for witnesses to be protected by legal instruments. The form of legal protection provided by the police is in the form of embezzlement of the identity of the complainant and not presenting witnesses in court. Efforts made by the police in providing legal protection for reporters of Narcotics and Psychotropics problems are by providing training to police officers on the operandi and distribution system of Narcotics and the types of Narcotics and the side effects they cause. Meanwhile, legal sanctions for reporters who know but do not report will be subject to legal sanctions Article 65 Law No. 5 of 1997 and for officers who do not shoot the witness' report can be subject to administrative sanctions in the form of a warning, scoring or transfer to police officers who do not announce the reporting report.